The Validity Of Notary’s Agreement Which Is Signed Outside The Notary’s Office - Dina Harindra Trisnani; Umar Ma'ruf (Jurnal Akta, 2018)
Article 19 paragraph (3), Article 3 paragraph 8 and Article 3 number 15 in Code of Ethics of Notary is a regulation governing the signing of notarial agreement at Notary's office. However, in practice, there is a case of signing the Agreement not in the Notary’s Office. The problem formulated is how the validity of notarial agreements signed not in the Notary's office and how the supervision of Notary in the signing of notarial agreement so that it is in accordance with notarial agreement. To answer the above problems, the author used normative research methods and a research approach; legal approach, conceptual approach, case approach and practical approach. Methods of data collection research used literature study method and the data were analyzed by qualitative analysis techniques and used deductive conclusions. According to the research, the validity of Notarial Agreement signed not at the Notary office has the following criteria; firstly, notarial agreements that are signed are not in the Notary's office but are still in the Notary's territory, the agreements are valid as long as there are special reasons. Secondly, notarial agreements signed not in the Notary office and not in positions of Notary's territory but still in the Notary's office area remain valid as long as it is done not sequentially and accompanied by specific reasons. Third, the Notary who signed the agreement not in his Notary's office and outside the territory of Notary Office, the agreement becomes invalid. Notary Supervision in signing of Notary Agreement pursuant to Notary Law and Notary Code of Indonesia is done by Supervisory Notary Board. Supervision by the Notary Board is done through preventive and curative activity including development activities. Supervision by Notary Board is done in two ways, namely: active supervision which checks Notary protocol and passive supervision which checks Notary statements.Keywords: Notary; Signing Agreement; Unnotary Office.